Analisis Dampak Bantuan Dana dan Modal Kerja Produktif BANPRES Terhadap Kinerja UMKM Dimasa Pandemi Covid-19 Di Kota Tasikmalaya - Wahid, Nisa Noor; Dermawan, Wildan Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the impact of financial assistance and productive working capital of BANPRES on the performance of MSMEs during the COVID-19 pandemic in Tasikmalaya City. The object of this research is micro, small and medium enterprises that receive BANPRES in the form of BPUM. The type of research used in this research is descriptive exploratory. Primary data are in-depth interviews and observations. The data analysis method used is exploratory descriptive analysis. the impact of additional capital in the form of assistance or loans does not directly but really helps MSMEs to improve their business performance. The results of the study stated that BPUM assistance recognized by Tasikmalaya City MSMEs in the form of additional capital had a positive impact on business performance. One of the perceived impacts of the additional capital assistance for MSMEs is the increasing ability in business and being able to compete through increasing products and increasing sales which ultimately increases profits. The impact that is felt is not direct, but it has a long lasting effect on the sustainability of its business.